Multicultural Dispute Resolution System in Aceh Before and After the Issuance of the Customary Institution Qanun - Mawar, Sitti; Iqbal, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The existence of customary institutions in Aceh has contributed significantly to the resolution of disputes in society. The existence of customary institutions has experienced ups and downs in accordance with the legal rules and regulations set by the government. This study is a normative legal study through a study based on the theory of legal pluralism, utilizing historical, conceptual, and comparative legal research techniques. The use of the theory of legal pluralism has recently been widely carried out through historical, conceptual, comparative, sociological and anthropological research on law. This study focuses on the multicultural settlement system in customary institutions before and after the enactment of Qanun Number 10 of 2008 in resolving household cases. The results of the study obtained by customary justice institutions in Aceh before and after the enactment of Qanun Customary institutions are the same, they still use local wisdom in resolving household disputes by prioritizing the customs of the community that have been established since the Indatu era, the difference with the issuance of qanun makes the function of the figure institution in its role in the customary institution clearer. The customary apparatus of Tuha peut Gampông is the party that plays a responsible role so that the resolution of the dispute/case does not cause losses to the parties, but makes maximum efforts to achieve peace. The leaders of customary institutions have the main responsibility of implementing the settlement process, deciding fairly, protecting the rights of the parties, recording the process and decisions and documenting documents. From the perspective of legal pluralism, dispute resolution through customary institutions is part of the recognition of the diversity of legal systems and the existence of customs in Aceh.